Grønlande og det moderne gennembruds mand - Haarder, Jon Helt (K&K - Kultur og Klasse, 2006)
Georg Brandes’ betydninger i Henrik Pontoppidans Lykke-Per, Grønlands i Isbjørnen Greenlands and man of the modern break-through Lykke-Per and Isbjørnen by Henrik Pontoppidan both seem to contain the author’s opinions on Georg Brandes and Greenland wrapped in fiction. By way of author theory and postcolonial criticism this article argues, however, that the two novels have no narratological or ideological central perspective. They are perhaps best understood as montages of discourses on Brandes and Greenland.